STUDY OF ENGINEERED CEMENTITIOUS COMPOSITE (ECC) CHARACTERISTICS WITH VARIATIONS OF CONTENT AND LENGTH OF SISAL FIBER - Sembiring, Suranta
Engineered Cementitious Concrete (ECC) or bendable concrete is one type of high performance concrete (HPC) with the constituent materials of fine aggregate, cement, silica fume, fly ash, superplasticizer, water, and the use of synthetic fibers up to a volume fraction of 2%. No coarse aggregate is used in ECC. With the use of fibers and elimination of coarse aggregate, ECC has deflection-hardening against bending and there is fiber-bridging in ECC cracks. The development of ECC in Indonesia has so far been limited by the use of synthetic fibers such as polymer fibers and steel fibers. Indonesia is rich in natural fibers, so in this study, synthetic fibers will be tried to be replaced with natural fibers from sisal. This study focuses on the mechanical characteristics of ECC or bendable concrete with variations in the amount of sisal fiber content (Agave Sisalana L.) namely 1% and 2% volume fraction and variations in the length of sisal fiber, namely 12 mm, 30 mm, and a combination of 12 mm and 30 mm. First, the tensile strength of the fiber was tested, which resulted in a tensile strength of sisal fiber of 335.35 MPa and an elongation of 15.6% of sisal fiber. Then, a fresh concrete test (slump test and slump loss) was carried out. From this test, it was found that the slump value was significantly affected by the number of fiber volume fractions used due to additional friction. Slump loss that occurs in fresh concrete ECC sisal fiber is 30-75% within 120 minutes. Furthermore, the hard concrete test was carried out to determine the compressive strength, modulus and Poisson's ratio and flexural strength of the ECC mixture. By referring to the mix design of ECC M45 by Lepech & Li (2008), it was found that the average compressive strength of ECC sisal fiber aged 28 days was 2.87-29.7 MPa. The very low compressive strength values in most of the specimens were due to the absorption of water by the fibers which was not considered during the initial mixing. The modulus value for 1% sisal fiber ECC is 22.17-23.40 GPa, significantly higher than the modulus value for 2% sisal fiber ECC which is 2.77-8.19 GPa. Poisson's ratio for ECC of 1% sisal fiber is 0.27-0.31, lower than Poisson's ratio for ECC of 2% sisal fiber of 0.32-0.40. The increase in flexural strength of sisal fiber ECC against non-fiber ECC was 8% from 3.7 MPa (Al-ameri, 2022) to 3.983 MPa based on the test. Adjustment of fiber water requirements is done by measuring the water absorption in the fiber and adding it to the mixture referring to the mix design based on Maalej (1994). The resulting compressive strength for the age of 14 days is 33.8 MPa to 41.6 MPa.